Analisis Nilai Karakter Religius dan Rasa Ingin Tahu dalam Buku Ajar Kimia Kelas X pada Materi Struktur Atom - Nurhabibah Nurhabibah; Ratih Permana Sari; Nurhafidhah Nurhafidhah (Universitas Samudra, 2021)
This study aims to determine the emergence of the values of religious character and curiosity contained in the chemistry textbook in high school class X on the atomic structure material. This study uses a qualitative approach with the type of content analysis research. The subjects of this study were chemistry teachers at the Langsa State Senior High School, namely SMA Negeri 2 Langsa, SMA Negeri 3 Langsa, SMA Negeri 3 Langsa, SMA Negeri 4 Langsa and SMA Negeri 5 Langsa. This research uses descriptive method with survey technique. Data collection techniques were carried out by interview and observation. Research activities use analytical techniques consisting of 6 steps, namely unitizing (determination of units), sampling (determination of samples), recording (recording or recording), reduction (reduction), inferring (drawing conclusions) and narrating (describes). The results showed that the emergence of religious character values in chemistry textbooks on atomic structure material was 11 sentences and the emergence of curiosity character values was 12 sentences. The author hopes that educators can choose textbooks that contain more character values in everyday life and parents do not hand over all character education to schools.